Sales Forecasting System Using Single Exponential Smoothing - Ketut Jaya Atmaja; Ida Bagus Gede Anandita (Jurnal Mantik, 2021)
In a trading business, meeting customer demand is very important to do. Fulfilling customer demand can be done with good stock inventory management. Accuracy in carrying out stock management is important to maintain the level of satisfaction of consumers because of the needs being met. In addition, accuracy in carrying out stock management can affect the financial cash flow of a trading business. Over-stocking, over time it will become dead-stock because the goods being sold become obsolete, changes in market tastes, not to mention merchandise that has an expiration date. Meanwhile, too little stock can cause lost of sales because the level of demand from consumers is greater than the amount of existing stock. Forecasting systems can help maximize stock inventory management in meeting customer demand needs. Forecasting is an activity in predicting and predicting something that will happen in the future. Forecasting is done through calculation analysis techniques based on past data references. This data can be in the form of qualitative data and quantitative data. The exponential smoothing method is a forecasting method based on qualitative data from a time series of previous sales trends to predict the future. This method is best used to analyze fluctuating sales trends. To determine the accuracy of forecasting, the results of the forecasting are then analyzed using the MSE and MAPE methods.